Topological importance of the segments of the technical system structure (Academic journal Industrial Machine Building Civil Engineering, 2021)
The article discusses the structure of a redundant technical system in the form of a graph. It is indicated that the structure of a technical system is modeled by an undirected graph. The most important and least important elements of this structure from the point of view of topology have been identified and substantiated. The distribution of the number of spanning trees and cyclic subgraphs passing through each element of the structure of the technical system is shown. The relative distribution of linked subgraphs by structure sections is given. This representation, together with the representation of the total number of related subgraphs, conveys the participation of elements in the connectivity of the technical system. The topological significance of the structure sections of the technical system is shown, taking into account the restrictions that this structure is multipolar.
Keywords: graph theory; system structure; structural reliability